To ban or not to ban carbon-intensive materials: A legal and administrative assessment of product carbon requirements - Timo Gerres; Manuel Haussner; Karsten Neuhoff; Alice Pirlot (Review of European, Comparative & International Environmental Law, 2021)
By setting near-zero-emission requirements for the production of certain products to be sold on the European single market (product carbon requirements, PCRs), the European Union could accelerate the phase-out of carbon-intensive production processes. The announcement of such requirements would send a signal to producers, financing institutions and other relevant stakeholders, thus incentivizing them to prepare for the shift to a carbon-neutral society. This article analyses several European environmental standards and technical regulations to offer insights into the political, legal and technical background for the adoption of PCRs. It shows that PCRs would constitute a new development in technical regulations. Given the relevance of World Trade Organization law for the adoption of standards and technical regulations on products, the article analyses in further detail the compatibility of PCRs under WTO law, and argues that PCRs can be designed in line with the provisions of the General Agreement on Tariffs and Trade and the Agreement on Technical Barriers to Trade.
Keywords: 330